Avaliação dos níveis de mercúrio total em músculos de peixes associados à macrófitas aquáticas do Rio Amazonas e afluentes – Amazônia, Brasil. - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2014)
The presence of mercury in various compartments of aquatic ecosystems is a worrying problem. The gold mining and mercury occurring naturally in the soil are known as sources responsible for this contamination. The mercury released into the environment can accumulate in the tissue of the aquatic animals and concentrations tend to increase as the animal gains weight and age in a phenomenon known as bioaccumulation. Once in the food chain biomagnificar mercury, and their concentrations amplified when passing from one trophic level to another just above. Thus, fish are often used as biological indicators of environmental contamination. This study aimed to investigate the bioaccumulation and biomagnification of total mercury in fish associated with aquatic macrophytes in a stretch of the Amazon River Basin. The collections were made in july and september 2012, six points located on the Amazon River and its tributaries. The collected fish were identified and had tissue samples taken for determination of total Hg using the technique of Cold Vapor Atomic Fluorescence (CVAFS). 50 species were analyzed and only 24% showed patterns of bioaccumulation of total Hg Just Acestrorhynchus falcirostris (523.6 ± 263.28) species showed values above the established by legislation with a total significantly higher than the other species (F 49, 730 = 6.04, p = 0.0000). The piscivorous, insectivorous, and zooplanctófagas planctófagas species reached higher concentrations in relation to other trophic levels. The Jurua and Japurá rivers were those with the greatest factors Biomagnification from producer to primary consumer with values (0.41638 and 0.40912) respectively. Being the point on the Amazon River near Manacapuru the only one to show positive Biomagnification. Most species are in total Hg levels below the limits established by brazilian legislation for human consumption, but some commercial and often consumed species exceeded the thresholds.
Keywords: Ecotoxicologia; Bioacumulação; Biomagnificação; Metilação; Perifíton; CNPQ: GEOCIÊNCIAS; RECURSOS NATURAIS; RECURSOS NATURAIS, BIODIVERSIDADE E BIOPROSTECÇÃO NA AMAZÔNIA; SOCIEDADE, NATUREZA E DESENVOLVIMENTO